A three-dimensional lattice Boltzmann method based reactive transport model to simulate changes in cement paste microstructure due to calcium leaching. (30th March 2018) - Patel, Ravi A.; Perko, Janez; Jacques, Diederik; De Schutter, Geert; Ye, Guang; Van Breugel, Klaas
Graphical abstract: Highlights: Model to simulate changes in cement paste microstructure due to leaching is presented. Reactive transport model using lattice Boltzmann method and takes 3D digitized microstructure as input. Leaching rate is found to be directly proportional to ability to transport calcium ions. Abstract: In this paper, a newly developed lattice Boltzmann method based reactive transport model to simulate changes in microstructure of ordinary Portland cement paste due to calcium leaching is presented. The model takes three-dimensional digitized cement paste microstructure as input and is capable to capture an evolution of microstructure due to leaching, accounting for the dissolution of portlandite and corresponding increase in capillary porosity and the decalcification of C-S-H resulting in increase in gel porosity. The developed model has been applied to microstructures generated using two cement hydration models, CEMHYD3D and HYMSOTRUC, for three water-to-cement ratios. It was observed that the rate of leaching is directly proportional to ability of microstructure to transport calcium ions and higher fraction of percolated capillary pores result in higher rate of leaching. The model qualitatively reproduces experimentally observed changes in cement paste porosity and pore size distribution due to leaching. The quantitative validation of model at this scale is not possible by comparison of leaching obtained experiments and simulations which can be attributed to several factors including the differences in the scales of experiment and modelling study presented in this paper.